ANALISIS KELAYAKAN USAHA BURUNG PUYUH PETELUR (Coturnix coturnix japonica) DI KELURAHAN TEBING TINGGI OKURA KECAMATAN RUMBAI PESISIR KOTA PEKANBARU - Boni Sanjaya; Amalia Amalia; Hamdan Yasid (Jurnal Ilmiah Pertanian, 2016)
This study aimed (1) to analyze the feasibility of livestock laying quail in Tebing Tinggi Okura Village, Rumbai Pesisir District, Pekanbaru city, namely in terms of the financial aspects of the investment criteria such as NPV (Net Present Value), Net B / CR (Net Benefit Cost Ratio), IRR (Internal Rate of Return) and PBP (Pay Back Period). (2) to analyze the feasibility of a laying quail farm in terms of aspects BEP (Break Event Point). (3) Knowing the problems faced by the businesses in the Tebing Tinggi Okura Village, Rumbai Pesisir District, Pekanbaru city. This research benefits to employers provide feedback input livestock farming quail analyze and give feedback to the relevant agencies in the development of quail farming in the future. The results of the study (1) Analysis of obtained investment criteria Net Present Value (NPV) Rp. 64,518,459, Internal Rate of Return (IRR) 18.94% Net Benefit Cost Ratio (Net B / C) 1.2. Of the three analysis shows the results of operations of livestock quail in the Tebing Tinggi Okura Village, Rumbai Pesisir District, Pekanbaru city well worth the effort and Pay Back Period (PBP) 2 years 7 months 27 days (2) Analysis of the feasibility of livestock quail from the aspect of Break Event Point (BEP) seen from the time period is 5 years 2 months 8 days, 3) Problems faced by entrepreneurs is a quail farm in the event of increased supply increases demand for quail eggs also increased so as to lower prices, usually occurs in the month of Ramadan. What happens is the tendency of declining revenues